Digital Literacy in Post-Pandemic Project Based Learning at Sekolah Kembang Jakarta - Gracia Adiati (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Digital literacy is an essential skill for students in learning in the post-pandemic digital era. This study aims to explore digital literacy for Sekolah Kembang students through group communication between teachers and students. The focus of the research is digital literacy in project based learning for elementary school students in grades 4, 5 and 6, and junior high school grades 7 and 8. In this study, the authors use qualitative approach with descriptive methods and data collection techniques through interviews. The results of the study show that digital literacy has become an integrated part of project based learning at the Sekolah Kembang. There are three communication patterns implemented in providing directions for finding and sorting information from the internet, which are large group communication, small group communication, and interpersonal communication. Identified group communication functions include persuasion, decision making, and problem solving. This research provides a better understanding of how digital literacy education can be implemented through communication between teachers and students at the Sekolah Kembang.